Decreased epithelial progesterone receptor A at the window of receptivity is required for preparation of the endometrium for embryo attachment†. Issue 2 (24th January 2017) - Wetendorf, Margeaux; Wu, San-Pin; Wang, Xiaoqiu; Creighton, Chad J.; Wang, Tianyuan; Lanz, Rainer B.; Blok, Leen; Tsai, Sophia Y.; Tsai, Ming-Jer; Lydon, John P.; DeMayo, Francesco J.
Abstract: The precise timing of progesterone signaling through its cognate receptor, the progesterone receptor (PGR), is critical for the establishment and maintenance of pregnancy. Loss of PGR expression in the murine uterine epithelium during the preimplantation period is a marker for uterine receptivity and embryo attachment. We hypothesized that the decrease in progesterone receptor A (PGRA) expression is necessary for successful embryo implantation. To test this hypothesis, a mouse model constitutively expressing PGRA ( mPgrA LsL /+ ) was generated. Expression of PGRA in all uterine compartments ( Pgr cre ) or uterine epithelium ( Wnt7a cre ) resulted in infertility with defects in embryo attachment and stromal decidualization. Expression of critical PGRA target genes, indian hedgehog, and amphiregulin ( Areg ), was maintained through the window of receptivity while the estrogen receptor target gene, the leukemia inhibitory factor ( Lif ), a key regulator of embryo receptivity, was decreased. Transcriptomic and cistromic analyses of the mouse uterus at day 4.5 of pregnancy identified an altered group of genes regulating molecular transport in the control of fluid and ion levels within the uterine interstitial space. Additionally, LIF and its cognate receptor, the leukemia inhibitory factor receptor (LIFR), exhibited PGR-binding events in regions upstream of the transcriptional start sites, suggesting PGRA is inhibiting transcription at these loci. Therefore, downregulation of the PGRA isoform at the window of receptivity is necessary for the attenuation of hedgehog signaling, transcriptional activation of LIF signaling, and modulation of solutes and fluid, producing a receptive environment for the attaching embryo. Summary Sentence: Expression of PGRA at the window of receptivity transcriptionally represses LIF signaling and aberrantly regulates hedgehog and solute signaling rendering the uterus unreceptive to the implanting embryo.